Clinical and microbiological profile of patients with diarrhea evaluated using the gastrointestinal panel in a high-complexity center - Jorge Andrés Salazar-Arenas; Leidy Johanna Hurtado-Bermúdez; Edgar David Salazar-Cardona; Nelson Enrique Rojas-Rojas; Juan Felipe Cubides-Martinez; Juan David Toro-Palma; Valeria Zúñiga-Restrepo; Carlos Arturo Rojas-Rodríguez (BMC Gastroenterology)
Abstract Introduction Gastrointestinal infections represent a worldwide public health problem. In Colombia, the incidence reaches 21.4 cases per 1,000 inhabitants. Given the limitations of traditional diagnostic methods in terms of sensitivity and specificity, the gastrointestinal panel (GIP) has emerged as a promising tool, allowing rapid detection of 22 pathogens. This study aimed to describe the clinical and microbiological characteristics of immunosuppressed and immunocompetent adult patients with diarrhea and the influence of the gastrointestinal panel in their treatment in a high-complexity hospital in Colombia. Materials and methods A cross-sectional observational study was carried out including 350 adult patients treated at the Fundación Valle del Lili hospital between 2021 and 2022. Demographic and clinical variables, GIP findings and treatment were analyzed by univariate and bivariate analysis. We compare immunocompromised and immunocompetent adult patients using Chi-square tests, Fisher’s F test for qualitative variables, Student’s t-test, and the Mann-Whitney U test for quantitative variables. A significance level of 5% was applied to demonstrate the significance of the variables in all the tests used. Results The results showed that 52% were men, with an average age of 52 years. 72.0% presented acute diarrhea, being inflammatory in 60.1%. 39.1% of the patients were immunosuppressed, mainly transplant recipients (31.3%). 53% of the GIPs were positive, with up to 5 pathogens per sample. Bacteria were detected in 80%, viruses in 14.4%, and parasites in 5.5%. The most frequent bacteria were enteropathogenic E. coli (43.0%), enteroaggregative E. coli (18.6%), and C. difficile (17.4%). Norovirus was the predominant virus (67.7%) and Cryptosporidium the most common parasite (41.7%). A higher frequency of Vibrio spp. was observed in non-immunosuppressed patients (p = 0.004) and of enterotoxigenic E. coli in immunosuppressed patients. 41.0% of patients received antibiotic/antiviral therapy, 83% empirically. GIP influenced the treatment of 56.7% of patients, with a 90.0% recovery rate. Conclusion This study confirms that GIP is a valuable diagnostic tool in the management of adult patients with diarrheal disease, particularly in immunocompromised patients. In our setting it is still a costly and difficult to access test, which makes it necessary to standardize the indications for its application. Future studies could evaluate its cost-effectiveness in our context.